P-AlInN electron blocking layer for AlGaN-based deep-ultraviolet light-emitting diode. (October 2021) - Sharif, Muhammad Nawaz; Niass, Mussaab Ibrahim; Liou, Juin J.; Wang, Fang; Liu, Yuhuai
Abstract: Commonly, the Al-rich AlGaN layer acts as electron blocking layer (EBL) to block the overflow of electrons from the active region in conventional AlGaN deep-ultraviolet (DUV) light-emitting diode (LED). However, the Al-rich AlGaN layer leads to the disadvantages of severe electron overflow and hole blocking effect. Herein, we proposed a new AlInN-based EBL to improve the optoelectronic characteristics of AlGaN-based DUV LED. The calculated results show that conventional (fixed Al composition) AlInN EBL has superior hole injection, reduced electron overflow, and lower electric field as compared to conventional AlGaN EBL. By using AlInN EBL, internal quantum efficiency (IQE) drop is reduced by 20%, and light output power improved by 165.30%. It was noticed that conventional AlInN EBL has a 28% IQE drop which can further be minimized by employing AlInN/AlInN superlattice EBL structure. It is found that superlattice EBL improved carrier distribution and reduced electric field resulting in a higher electron-hole wave-function overlap of 55% within multiple quantum wells (MQW) which elevate radiative recombination rate. AlInN superlattice EBL LED has drop-free 93% IQE, twice light output power, and spontaneous emission rate compared to conventional AlInN EBL LED. Highlights: AlInN-based EBL is used to improve the optoelectronic characteristics of AlGaN-based DUV LED. Conventional (fixed Al composition) AlInN EBL has superior hole injection, reduced electron overflow, and lower electric field as compared to conventional. AlInN superlattice EBL LED has drop-free IQE, twice light output power, and spontaneous emission rate compared to conventional AlInN EBL LED.